#### Answer

$y' = -2e^{-x}+3e^{3x}$

#### Work Step by Step

$y= 2e^{-x} +e^{3x}$
$y' = -2e^{-x}+3e^{3x}$

Published by
Pearson

ISBN 10:
0321999584

ISBN 13:
978-0-32199-958-0

$y' = -2e^{-x}+3e^{3x}$

$y= 2e^{-x} +e^{3x}$
$y' = -2e^{-x}+3e^{3x}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.